Teaching of Speech Acts: Suggestions regarding Methodology - Duyvene de Wit, Helene E; Ntuli, R M (South African Journal of African Languages, 1997)
Methodological problems concerning the teaching of speech acts to adult native-Afrikaans-speaking learners of indigenous African languages in South Africa are addressed. Characteristics of a communicative approach derived from the functional-notional approach are described, focusing on the production of authentic, coherent discourse with emphasis on fluency rather than grammatical accuracy. An attempt is made to apply these principles within the framework of the four-phased learning cycle as proposed by D. A. Kolb (1984), ie, (1) concrete experience & reflective observation, (2) reflective observation & abstract conceptualizing, (3) abstract conceptualizing & active experimenting, & (4) active experimenting & concrete experience. Methodological options for each phase are offered, stressing the move from reception to production implicit in the learning cycle; the process is illustrated with a Zulu dialogue designed for adult learners of Zulu. 3 Figures, 46 References. Adapted from the source document